Differential effects of prolonged post-fixation on immunohistochemical and histochemical staining for postmortem human brains - Weiya Ma; Eve-Marie Frigon; Josefina Maranzano; Josefina Maranzano; Yashar Zeighami; Yashar Zeighami; Mahsa Dadar; Mahsa Dadar (Frontiers Media S.A., 2024)
PurposeImmunohistochemical (IHC) and histochemical (HC) staining techniques are widely used on human brains that are post-fixed in formalin and stored in brain banks worldwide for varying durations, from months to decades. Understanding the effects of prolonged post-fixation, postmortem interval (PMI), and age on these staining procedures is important for accurately interpreting their outcomes, thereby improving the diagnosis and research of brain disorders afflicting millions of people worldwide.MethodsIn this study, we conducted both IHC and HC staining on the prefrontal cortex of postmortem human brains post-fixed for 1, 5, 10, 15, and 20 years. For IHC staining, we used two antibodies for each marker: the neuron marker neuronal nuclear antigen (NeuN), the astrocyte marker glial fibrillary acidic protein (GFAP), and the microglia marker ionized calcium-binding adaptor molecule 1 (Iba1). For HC staining, we conducted hematoxylin and eosin Y (H&E), cresyl violet (CV), and Luxol fast blue (LFB) stains to examine neuropils, neurons, and myelin, respectively.ResultsWe observed that the intensity of NeuN, Iba1, CV, or LFB staining was negatively correlated with post-fixation durations. Conversely, we detected a positive correlation between the intensity of GFAP and H&E staining and post-fixation durations. Moreover, there was no correlation between the intensity of NeuN, GFAP, Iba1, H&E, CV, and LFB staining and PMI. Additionally, no correlation was found between these staining intensities and age, except for the intensity of GFAP immunostained by one antiserum, which was negatively correlated with age.ConclusionTaken together, these findings suggest that prolonged post-fixation has both positive and negative effects, while age and PMI exert limited influence on these IHC and HC parameters. Therefore, it is essential to consider these differential changes when interpreting results derived from tissues with extended post-fixation durations. Furthermore, if feasible, we recommend conducting IHC and HC staining on human brains with the same post-fixation time spans and using the most optimal antibodies to mitigate the impact on subsequent analyses.